Beliefs of University Employees Leaving During a Fire Alarm: A Theory-based Belief Elicitation - Christopher Owens; Aurora B. Le; Todd D. Smith; Susan E. Middlestadt (Elsevier, 2023)
Background: Despite workplaces having policies on fire evacuation, many employees still fail to evacuate when there is a fire alarm. The Reasoned Action Approach is designed to reveal the beliefs underlying people's behavioral decisions and thus suggests causal determinants to be addressed with interventions designed to facilitate behavior. This study is a uses a Reasoned Action Approach salient belief elicitation to identify university employees' perceived advantages/disadvantages, approvers/disapprovers, and facilitators/barriers toward them leaving the office building immediately the next time they hear a fire alarm at work. Methods: Employees at a large public United States Midwestern university completed an online cross-sectional survey. A descriptive analysis of the demographic and background variables was completed, and a six-step inductive content analysis of the open-ended responses was conducted to identify beliefs about leaving during a fire alarm. Results: Regarding consequence, participants perceived that immediately leaving during a fire alarm at work had more disadvantages than advantages, such as low risk perception. Regarding referents, supervisors and coworkers were significant approvers with intention to leave immediately. None of the perceived advantages were significant with intention. Participants listed access and risk perception as significant circumstances with the intention to evacuate immediately. Conclusion: Norms and risk perceptions are key determinants that may influence employees to evacuate immediately during a fire alarm at work. Normative-based and attitude-based interventions may prove effective in increasing the fire safety practices of employees.